The shredded voices from the torn land / Dr. Anis Shaari - Shaari, Anis (Academy of Language Studies, 2024)
As we listen into the dark night, unseeing … [for everything is blackened] The elderly are gasping, The children are screaming To our best, so hard we are trying Building courage out of rubbles Singing prayers out of tears Does the world not hear us?